Relationship between Cardiometabolic index and endometriosis in a US nationally representative sample: results from NHANES 1999-2006 - Hou, Jiarui; Chen, Wenting; Wang, Rui; Huang, Xuchun; Cao, Xiaojing; Wang, Xiaoyun (Frontiers in Endocrinology, 2024)
BACKGROUND：Endometriosis is an estrogen-dependent gynecological endocrine condition and a systemic inflammatory disease associated to improper lipid metabolism and increased cardiovascular risk. The Cardiometabolic Index (CMI) is a novel indicator representing visceral adipose tissue distribution and metabolic dysfunction, integrating lipid metabolism indicators and the waist-to-height ratio. While anomalies in lipid metabolism are often associated with (BMI) Body Mass Index, literature consistently shows a negative link between endometriosis and female BMI, and some studies have found that endometriosis is one of the few reproductive diseases not persistently positively correlated with obesity. Given the limitations of BMI, a comprehensive